2019
DOI: 10.20961/carakatani.v35i1.33618
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phosphorus and Potassium on the Growth and Quality of Viola (Viola cornuta L.) Seed Production

Abstract: <p>Viola cornuta L. is an ornamental plant that is primarily propagated by high-quality seeds that have high demand in subtropical countries. The use of fertilizers according to recommendations results in the growth of parent plants below the standard. Furthermore, seed production is generated below 2 g per plant and the seed germination capacity is below 80%. In addition, phosphorus (P) and potassium (K) nutrients can increase the growth and seed production of the plants, including ornamental plants. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…This is in line with the results of other studies, where phosphorus availability is significantly correlated with grain yield [39], [40]. Furthermore, phosphorus is involved in several metabolic processes of plants and energy production [41]. Plants need the energy for metabolic processes such as photosynthesis, where the results affect plant growth.…”
Section: Resultssupporting
confidence: 91%
“…This is in line with the results of other studies, where phosphorus availability is significantly correlated with grain yield [39], [40]. Furthermore, phosphorus is involved in several metabolic processes of plants and energy production [41]. Plants need the energy for metabolic processes such as photosynthesis, where the results affect plant growth.…”
Section: Resultssupporting
confidence: 91%
“…As investigated in this study, we could observe that fertiliser blends using recovered nutrients such as P from struvite and N as ammonium nitrate can successfully substitute the use of mineral fertiliser blends to grow ornamental plant species such as viola, as has been previously shown in other horticulture plants [33]. Still, preparing green and sustainable fertiliser blends based on recovered nutrients from various waste streams requires exhaustive control and knowledge of every nutrient added [34]. This includes the careful and clean mining of the nutrients as well as the understanding of the fertilising effects on the desired target plants.…”
Section: Discussionsupporting
confidence: 57%
“…This is in line with Liu et al (2020), which reported that the combined application of long-term organic and inorganic nitrogen fertilizers improves the physicochemical properties of the soil and increases the soil's organic carbon and nitrogen content. The weight of tomato fruit is associated with the macronutrients contained in the plant, especially P. Saputra et al (2019) reported that P and K nutrients affected height, number of flowers, number of seeds per capsule, seed production, and germination energy and significantly affect the number of the leaf. Table 3, tomato fruit weight in P3 and P2 treatments was higher since the macronutrient was applied.…”
Section: Discussionmentioning
confidence: 99%